Retributivism has a past has it a future? - Tonry, Michael H. (New York ; Oxford : Oxford University Press, 2011)
A collection of essays by major figures in punishment theory law, and philosophy that reconsiders the popularity and prospects of retributivism, the notion that punishment is morally justified because people have behaved wrongly.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Punishment -- Philosophy; Retribution